2020
DOI: 10.11591/ijphs.v9i2.20388
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to increase nutritional status among Cytomegalovirus (CMV) infected children

Abstract: <span>Malnutrition has an interrelated relationship with infectious diseases, where infection can occur malnutrition and can cause malnutrition in children. Children who infected with CMV need an increase in nutritional status, but with malnutrition, the recovery process and the body's immune enhancement cannot be optimal. This study aimed to identify the efforts to improve the nutritional status of children infected with CMV in Tegal, Central Java, Indonesia. This study was a qualitative study with phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It is observed that inadequate knowledge of kindergarten teachers and management can cause picky eating habits in the pre-schoolers, illogical nutrition management, and irrational allocation of various nutrients. Poor nutrition habits open the doors to multiple infections which in turn can worsen the malnutrition, thus starting a vicious cycle [3]. Efforts to improve the knowledge of kindergarten teachers can bring change in the nutrition awareness of these pre-schoolers [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that inadequate knowledge of kindergarten teachers and management can cause picky eating habits in the pre-schoolers, illogical nutrition management, and irrational allocation of various nutrients. Poor nutrition habits open the doors to multiple infections which in turn can worsen the malnutrition, thus starting a vicious cycle [3]. Efforts to improve the knowledge of kindergarten teachers can bring change in the nutrition awareness of these pre-schoolers [4].…”
Section: Introductionmentioning
confidence: 99%